(3ZGjI GdCed aj JbOjQ GdYeds - (3GdCfUGQj GdChSj, GHf SYO, Ydj Hf EHQGgje Hf NVQ, Hf eQga, J (B766(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj ef Ydi ef GLJHi ef YHGOg HGdgOi aEfj CPcQ hab Gddg JYGdi aj gPG GdLRA eGdGHO efg aChba ajg Ydi eGde jag Hg aGVd eef JbOe EdG eTjQG CbUO aj Pdc cTa GdMb s
(3BNQgG (B:s
(3aEfg jfNd RFHbG eHGQcG abGdG aGYbO HLhGQg fGQ dWjaI MJi jfYbO MLQG CHjVG QMGejG aCdb efg Ydi GdRgQI GdefbGI HCMO hcd MdGdG WjHG YLdG hGSJYf HPdc Ydi GdYed GcHjQ GdebUhO HGdPGJ hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdOQQ GdcGefI aj CYjGf GdeGFI GdKGefI (B4\4s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdcjejGA hGdWHjYjGJs